Offline is the New Fun: Kampanye Kreatif Digital Detox untuk Generasi Z di SMP Al Azhar Syifa Budi Surakarta - Kusciati, Karunia; Fitria Akhmerti Primasita; Muhammad Taufiq Al-Makmun; Yusuf Kurniawan; Diah Kristina (J-Dinamika : Jurnal Pengabdian Masyarakat, 2026)
The purpose of the digital detox creative campaign for Generation Z at Al Azhar Syifa Budi Junior High School Surakarta is to encourage students to reduce gadget usage or undergo digital detox in a fun and creative way, namely through a digital detox social media campaign. Dependence on gadgets can lead to negative effects on both physical and mental health, such as anxiety, difficulty in concentrating, and mental disorders. The students of Al Azhar Syifa Budi Surakarta Junior High School participated in four sessions of digital detox training along with social media campaign training in an enjoyable manner. They were introduced to the importance of digital detox and fun ways to carry it out, such as playing games. They then shared the knowledge about digital detox during the training through social media in the form of a social media campaign. By spreading the importance of digital detox through social media, they not only learned to practice digital detox and benefit from it themselves but also became the agents of change.